2015
DOI: 10.1038/ncomms7277
|View full text |Cite
|
Sign up to set email alerts
|

Experimental diagenesis of organo-mineral structures formed by microaerophilic Fe(II)-oxidizing bacteria

Abstract: Twisted stalks are organo-mineral structures produced by some microaerophilic Fe(II)-oxidizing bacteria at O 2 concentrations as low as 3 mM. The presence of these structures in rocks having experienced a diagenetic history could indicate microbial Fe(II)-oxidizing activity as well as localized abundance of oxygen at the time of sediment deposition. Here we use spectroscopy and analytical microscopy to evaluate if-and what kind of-transformations occur in twisted stalks through experimental diagenesis. Unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 66 publications
8
85
2
Order By: Relevance
“…As for all laboratory simulations, the present experiments do not exactly mimic what really occurs in natural settings during millions of years 22, 25, 29, 31, 3335 . Biodegradation and early taphonomic processes that may occur within sediments have not been simulated here, even though they may also alter the chemical composition of organic materials before the beginning of thermal maturation 14, 56 .…”
Section: Discussionmentioning
confidence: 59%
“…As for all laboratory simulations, the present experiments do not exactly mimic what really occurs in natural settings during millions of years 22, 25, 29, 31, 3335 . Biodegradation and early taphonomic processes that may occur within sediments have not been simulated here, even though they may also alter the chemical composition of organic materials before the beginning of thermal maturation 14, 56 .…”
Section: Discussionmentioning
confidence: 59%
“…In the organic carbon fraction of the twisted stalks, we found polysaccharides, saturated aliphatic compounds (most probably lipids), and a very small amount of protein. Similar compounds have been detected in stalks of other marine and also freshwater microaerophilic Fe(II)-oxidizing bacteria, but not all authors detected lipids (29,(32)(33)(34)(35). The indication of membrane lipids we found by FTIR could be due to the adsorption of cellular material, which might also be true for the detected protein.…”
Section: Figmentioning
confidence: 59%
“…saccharides, saturated lipids, and a small amount of protein (29,(32)(33)(34)(35). However, more detailed information on the exact nature of these organic compounds is so far lacking.…”
mentioning
confidence: 99%
“…Fe oxide stalks from freshwater mats have been shown to survive metamorphic conditions similar to those of the least metamorphosed BIFs (Picard et al, 2015). Indeed, stalk-like morphologies have been observed in the rock record (Hofmann & Farmer, 2000;Little et al, 2004;Slack et al, 2007), although stalks have not yet been observed in BIFs.…”
Section: Fe Microbial Matsmentioning
confidence: 99%